ANALYSIS OF THE BRAND IMAGE OF THE LEMBAH HIJAU TOURIST ATTRACTION IN EAST LOMBOK REGENCY - Mayasni, Yayuk; Septiana, Rini; Riadi, Selamat (Fakultas Agama Islam Universitas Islam Al-Azhar, 2025)
This study analyzes the brand image of the Lembah Hijau tourist attraction in East Lombok Regency by examining aspects such as favorability, strength, and uniqueness of brand associations. The research employs a qualitative approach with descriptive analysis, focusing on Ijobalit Village where the attraction is located. Data were collected through interviews with nine informants who possess substantial knowledge about Lembah Hijau. Findings indicate that while accessibility is convenient and the attraction's name is easy to remember and pronounce, facilities are insufficient, and maintenance is suboptimal. Although the environment offers picturesque, safe, and serene views, visitor services require improvement. The study suggests optimizing promotional strategies to increase awareness across local and external communities.